Study on incidence of lamb morbidity and mortality and associated risk factors in the mixed crop-livestock production system of Gewata District, Kaffa zone, southwestern Ethiopia - Haben Fesseha; Gizaw Gebremichael; Isayas Asefa; Teshita Edaso (BMC, 2023)
Abstract Lamb morbidity and mortality cause significant loss in a smallholder production system. A longitudinal prospective survey was conducted on 408 randomly selected farmers located in six purposefully selected kebeles in Gewata woreda from June 2020 to July 2021 to determine the incidence of morbidity and mortality in lambs and to identify risk factors. For this purpose, 408 lambs from the Gewata district's mixed crop-livestock production system were examined every day from birth to three months of age. The data was analyzed using the Kaplan-Meier (K-M) method, the log-rank test, and Cox proportional hazards regression. Results showed that the cumulative incidence of all-cause of morbidity and mortality at the end of three month was 12.86% (95% CI: 10.26-16.13%), and 6.86% (95% CI: 5.03-9.35%), respectively. Diarrhea was the leading cause of morbidity and mortality, accounting for 49.33 and 50% morbidity and mortality, respectively. Pneumonia was the second most frequent cause of morbidity and death. In the K-M hazard analysis, the greatest risk of lamb morbidity and mortality was observed during the first month of life, and then the risk decreased significantly as the lamb grew. Of the 17 potential risk factors studied, the multivariable Cox proportional hazards regression model showed that lamb sex, birth weight, umbilical care, time and method of colostrum feeding were the five predictors that were significantly associated with a higher risk of morbidity, whereas birth weight, lambing difficulty, dams' parity, method and time of colostrum feeding were the five predictors that were significantly associated with a higher risk of mortality. Moreover, a higher risk of morbidity was observed in lambs with methods of colostrum feeding after birth (HR = 3.158; p = 0.000) and with variations in birth weight (HR = 1.418; p = 0.003). Similarly, the mortality risk was 4.926 (p = 0.047), 4.023 (p = 0.012), and 3.206 (p = 0.000) times higher in lambs with lambing difficulties, at the time of colostrum feeding, and by the method of colostrum feeding, respectively. According to this research, lamb morbidity and mortality rates in the study area are significantly high which has a great impact on the replacement stock and production. Hence, awareness should be created among farmers concerning improved lamb management practices.